Tapered Optical Fiber Sensor for Discrimination of Strain and Temperature - Mustafa Bilsel (Advances in Electrical and Electronic Engineering, 2020)
A simple Mach-Zehnder interferometer (MZI) based on a standard single-mode fiber for simultaneous strain and temperature sensing was proposed and demonstrated experimentally. The interferometer was fabricated by electrical arc discharge method in which a portion of the standard single-mode fiber was heated and stretched. Any special type of fiber or a particular splicer was not required to form the MZI and it indicated high resolution. To find the modes that contributed to the interference spectrum, Fourier analysis was done and the spatial frequency versus normalized intensity plot showed that LP02 was the excited dominant higher order cladding mode. Coefficient matrix was realized for simultaneous measurement of strain and temperature ability of such an MZI. For discrete measurements, a resolution of 0.79 °C in temperature and 1.18 micro-strain can be achieved for 10 pm wavelength resolution. This extremely simple, low-cost sensor easily fabricated with good repeatability is a good candidate in diverse sensing applications.